Karakteristik dan paradigma al-qur’an dan sosial budaya - Pertiwi, Safira Ramadhani (Maliki Interdisciplinary Journal, 2025)
This article discusses the characteristics and paradigm of the Living Qur'an, an approach that emphasizes understanding and applying the teachings of the Qur'an in daily life. The Living Qur'an has several key characteristics, including the integration of Qur'anic teachings with aspects of morality and ethics in social interactions, contextual interpretations relevant to the times, and a harmonious relationship with science. In addition, this concept encourages continuous spiritual practice and social and environmental responsibility. In terms of paradigm, Living Qur'an promotes humanistic theology, value-based leadership, holistic education, tolerance, and environmental preservation. Thus, Living Qur'an functions not only as a sacred text, but also as a dynamic and applicable guide for life, which aims to create a better and more just society.